Taking Stock, August 2022 : Educate to Grow - World Bank (Washington, DC, 2022)
As the two-year Coronavirus (COVID-19) crisis appears to wane, new economic shocks have cast shadows over the global economy heightening uncertainty about the short-to-medium path to recovery. The supply shock associated with the war in Ukraine is expected to blunt the promising economic recovery around the world and has raised the specter of stagflation in advanced countries, leading to tightening conditions in global financial markets. Measures undertaken by China to control the spread of the Omicron variant of COVID-19 are also impacting its growth and the performance of global value chains. Additional risks threaten the recovery prospects of the global economy. New COVID-19 variants continue to be a severe risk, and as people around the world grow weary of pandemic-measures, this ‘fatigue’ could hamper attempts at controlling the spread. Vietnam’s economy is rebounding after two bruising years but faces domestic challenges and an unfavorable external environment in the short-to-medium-term. High vaccination rates facilitated the re-opening of the Vietnamese economy after the lockdowns of Q3-2021. Chapter 1 of this Taking Stock report reviews the recent developments in Vietnam’s economy and assesses its short-to-medium term prospects. It examines the country’s growth performance, its external balance, and monetary and fiscal policy responses during the first half of 2022. Chapter 2 reviews the performance in tertiary education access and outcomes.